MOBILE LEARNING APPLICATION BERBASIS ANDROID : PERAN GURU DALAM PEMBELAJARAN PESERTA DIDIK GEN Z & ALFA - Churiyah, Madziatul; Subagyo, Subagyo; Basuki, Andi; Dharma, Buyung Adi; Filianti, Filianti; Sakdiyyah, Dewi Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Universitas Negeri Malang, 2020)
Abstrak: Peserta didik saat ini merupakan generasi Z dan Alfa yang memiliki karakteristik sebagai digital native, dimana kehidupan mereka sangat lekat dengan teknologi digital, terutama device android. Saat ini pun sedang terjadi situasi pandemi covid-19 yang menuntut agar pembelajaran dilakukan secara jarak jauh. Berdasarkan hal ini, dibutuhkan media pembelajaran berbasis android dan diharapkan guru dapat mengembangkannya. Akan tetapi, pembuatan media pembelajaran berbasis android terkenal susah karena guru harus memahami ilmu coding yang rumit terlebih dahulu. Melihat realitas tersebut, dilakukan pelatihan nasional kepada guru senusantara untuk mengembangkan mobile learning application berbasis android yang akan digunakan sebagai media pembelajaran. Pelatihan dilakukan secara virtual melalui live stremaing YouTube serta bimbingan intensif oleh instruktur di kelas pada Google Classroom selama satu bulan. Hasil pengabdian menunjukkan para peserta mampu mengembangkan mobile learning application berbasis android tanpa coding untuk mata pelajaran yang diampunya, kemudian menggunakannya sebagai tool dalam melaksanakan remote learning di situasi pandemi covid-19. Hasil diskusi bersama peserta pelatihan, peserta didik mereka merasa tertarik dan antusias dalam menggunakan mobile learning application yang telah dikembangkan oleh guru.Abstract: Students are currently generation Z and Alfa who have the characteristics of being digital native, where their lives are very closely related to digital technology, especially Android devices. Currently there is also a Covid-19 pandemic situation which demands that learning be carried out remotely. Based on this, android-based learning media is needed and it is hoped that teachers can develop it. However, making Android-based learning media is notoriously difficult because teachers must first understand complex coding. Seeing this reality, a national training was conducted for Indonesian teachers to develop an Android-based mobile learning application that will be used as a learning medium. The training is conducted virtually through YouTube live stremaing as well as intensive guidance by instructors in classes at Google Classroom for one month. The results of this dedication show that the participants are able to develop an Android-based mobile learning application without coding for the subjects they are teaching, then use it as a tool in implementing remote learning in the Covid-19 pandemic situation. The results of the discussion with the training participants, their students felt interested and enthusiastic in using the mobile learning application that had been developed by the teacher. then use it as a tool in implementing remote learning in the covid-19 pandemic situation. The results of the discussion with the training participants, their students felt interested and enthusiastic in using the mobile learning application that had been developed by the teacher. then use it as a tool in implementing remote learning in the covid-19 pandemic situation. The results of the discussion with the training participants, their students felt interested and enthusiastic in using the mobile learning application that had been developed by the teacher.Â